Konsep Diri Gamers MOBA yang Mengalami IGD - Agnia Restu Gunawati; Fanni Putri Diantina (Bandung Conference Series: Psychology Science, 2022)
Abstract. Online games grow rapidly every year. The population of Indonesian gamers is approximately 52 million users, where one of the most popular games is MOBA (multiple online battle arena). Gamers who are too fixated on online games have the opportunity to experience internet gaming disorder (IGD). One of the risk factors for the disorder is self-concept. Moreover, data for this study were collected by following the rule from the Tennessee Self Concept Scale (TSCS) developed by W.H. Fitts (1965) and Game Addiction Scale (GAS) developed by Lemmens et al. (2009). The sample of respondents (n=291) for this study is MOBA gamers in Bandung. The methodological approach taken in this analysis is quantitative causality and analyzes the data using descriptive. The results showed that most of MOBA gamers had a negative self-concept as many as 177 people (60.82%) and experienced moderate addiction as many as 172 people (59.11%). In addition, in this study, MOBA gamers were dominated by male and adolescent gamers, 59.11% and 94.16% respectively Abstrak. Perkembangan game online sangat pesat dan mengalami lonjakan jumlah gamers setiap tahunnya. Pada tahun 2019, gamers di Indonesia mencapai 52 juta orang. MOBA (multiple online battle arena) adalah genre game yang paling diminati. Gamers yang terlalu terpaku pada game online berpeluang mengalami internet gaming disorder (IGD). Salah satu faktor resiko seseorang menjadi IGD adalah konsep diri. Pengumpulan data menggunakan skala Tennessee Self Concept Scale (TSCS) yang dikembangkan W.H. Fitts (1965) dan Game Addiction Scale (GAS) yang dikembangkan Lemmens, et.al (2009). Sampel yang menjadi responden adalah gamers MOBA di Bandung sejumlah 291 orang. Metode pada penelitian ini adalah kuantitatif kausalitas dan analisis data menggunakan analisis deskriptif. Hasil penelitian menunjukan sebagian besar gamers MOBA memiliki konsep diri yang negatif sebanyak 177 orang (60,82%) dan mengalami adiksi tingkat sedang sebanyak 172 orang (59,11%). Selain itu, pada penelitian ini gamers MOBA didominasi oleh gamers laki-laki dan berusia remaja, masing-masing 59,11% dan 94,16%.